A IDENTIFICATION AND UTILIZATION OF WASTE MATERIALS IN THE FOLLOW-UP PROJECT OF TALUD CONSTRUCTION OF SYUKURAN AMINUDDIN AMIR LUWUK BANGGAI AIRPORT: IDENTIFICATION AND UTILIZATION OF WASTE MATERIALS IN THE FOLLOW-UP PROJECT OF TALUD CONSTRUCTION OF SYUKURAN AMINUDDIN AMIR LUWUK BANGGAI AIRPORT - Rusman, Hendra Jultrisno; Basiri, Syamsu; Sari, Eka Citra (SIPARSTIKA: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2023)
The Regional Government of Banggai Regency is currently building the Banggai Amiruddin Amir Luwuk Banggai Thanksgiving Airport with the goal of enhancing facilities and infrastructure to support air transportation, and one of the things being done is to continue the construction of the talud. According to PPRI No. 22 Th. 2021 and PermenLHK No. 18 Th. 2021, waste material management can be done utilizing the 4R approach, which stands for (1) Reduce, (2) Reuse, (3) Recycle, and (4) Repair, respectively. Formwork, excavation, building an embankment, installing reinforcement, casting, and talud plastering are the stages of the project. The identification's findings demonstrate that errors in construction management and budget management commonly result in residual materials including cement, wood, dirt, iron, sand, and gravel at all stages of the job. Utilizing the reduction technique, project implementers minimize the existence of residual material by managing the construction process and project budget effectively. While cement can only be minimized through the reduce process, management of the ensuing residual materials, such as wood, soil, iron, sand, and gravel, is carried out using the reuse and recycle approach.